COLLABORATIVE PROJECT-BASED TRANSLATION IN BILINGUAL MENU BOOKLETS: METACOGNITION AND CULTURAL CHALLENGES - Rahmadila Eka Putri; Mutia Nasution; Sulistya Ningrum (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2026)
This study investigated collaborative project-based translation of bilingual Indonesian–English menu booklets as a pedagogical context where linguistic, cultural, and cognitive demands intersect. Central to this process was students’ metacognitive awareness, which regulates how they plan, monitor, negotiate, and revise translation decisions when confronting culturally embedded culinary texts. Although menu translation plays a crucial role in culinary tourism and intercultural communication, its pedagogical implementation particularly through collaborative Project-Based Learning (PjBL) frameworks foregrounding metacognitive strategy use remains underexplored in translation studies. Addressing this gap, the study adopted a qualitative case study design grounded in constructivist pedagogy and PjBL. Twenty vocational higher education students were purposively selected and divided into five collaborative groups, each assigned to translate a themed Indonesian menu (vegan, fusion food, sweets, street food, and seafood) into a bilingual booklet. Data were triangulated from student-produced menu booklets, non-participant classroom observations, and semi-structured interviews, and analyzed using thematic and document analysis. The findings reveal persistent challenges related to culture-specific culinary terms, lexical gaps, and tensions between cultural authenticity and communicative clarity. To address these challenges, students employed metacognitive strategies such as strategic planning, peer negotiation, self-monitoring, and reflective revision, alongside translation techniques including descriptive equivalence, borrowing, amplification, and literal translation. However, uneven application of these strategies exposed conflicts between domestication and foreignization, and between linguistic accuracy and audience accessibility. Despite limitations such as inconsistent terminology, unequal participation, and absence of authentic client feedback, collaborative project-based translation enhanced students’ translation competence by fostering metacognitive awareness, intercultural sensitivity, and multimodal design skills.